2008
DOI: 10.1038/cdd.2008.146
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP A1 regulates UV-induced NF-κB signalling through destabilization of cIAP1 mRNA

Abstract: cIAP1 is an important member of the inhibitor of apoptosis family of proteins and is involved in the regulation of the NF-jBsignalling pathway downstream of the TNF receptor. We report here that UV irradiation leads to downregulation of cIAP1 expression because of enhanced cIAP1 mRNA destabilization. An AU-rich element located within the 3 0 untranslated region of cIAP1 mRNA is sufficient to mediate cIAP1 mRNA instability. Furthermore, we have identified hnRNP A1 as a cIAP1 3 0 UTR-binding protein. hnRNP A1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…22,23 cIAP1 expression may be regulated by ubiquitination, degradation, or mRNA destabilization. 24 The mechanism of cIAP1 upregulation in neurons and endothelial cells after IP remains unclear. Our previous study showed that IP-induced cyclic AMP response element binding protein activation in neonatal brain.…”
Section: Strokementioning
confidence: 99%
“…22,23 cIAP1 expression may be regulated by ubiquitination, degradation, or mRNA destabilization. 24 The mechanism of cIAP1 upregulation in neurons and endothelial cells after IP remains unclear. Our previous study showed that IP-induced cyclic AMP response element binding protein activation in neonatal brain.…”
Section: Strokementioning
confidence: 99%
“…Following centrifugation to remove debris, we precleared the lysate before immunoprecipitation with Pansorbin cells for 2 h at 4°C (EMD Chemicals, Gibbstown, NJ, USA). Co-immunoprecipitation of cIAP1 and β -actin from the precleared lysates was performed at 4°C for 16 h using Protein G/ Protein A-Agarose beads (EMD Chemicals) coated with antibodies specific for β -actin (Sigma-Aldrich) and cIAP1 45 at a titer of 1 : 500 and 1 : 150, respectively. The beads were then washed extensively with cold wash buffer (50 mM Tris (pH 7.4), 300 mM NaCl, 0.1% Triton X-100), resuspended in Laemmli buffer and boiled to elute bound proteins.…”
Section: Methodsmentioning
confidence: 99%
“…hnRNP A1, the AUBP that was shown to compete with AUF1 for binding to the EV71 IRES, is a multifunctional protein involved in transcription, alternative splicing, mRNA localization, translation, and stability [143]. hnRNP A1 has been reported to destabilize mRNAs bearing AREs [144] or an ARE-like motif (a motif which was identified in ~7% of mRNAs) [145]. However, instead of destabilizing EV71 RNA, hnRNP A1 is re-purposed by the virus as a positive regulator of translation [135].…”
Section: Adenylate Uridylate-rich Element (Are)-mediated Mrna Decamentioning
confidence: 99%